2008
DOI: 10.5511/plantbiotechnology.25.45
|View full text |Cite
|
Sign up to set email alerts
|

Chimeric AGAMOUS repressor induces serrated petal phenotype in Torenia fournieri similar to that induced by cytokinin application

Abstract: The homeotic protein AGAMOUS (AG) terminates the floral meristem and promotes the development of stamens and carpels in Arabidopsis. Disruption of its function or expression of the chimeric AG repressor (AGSRDX) results in redundant petals, known as a double flower phenotype. To investigate whether this morphological change in Arabidopsis is applicable to ornamental flowers to increase their horticultural value, we introduced AGSRDX into torenia (Torenia fournieri Lind.) plants. Transgenic torenia plants expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
14
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 38 publications
(54 reference statements)
2
14
0
Order By: Relevance
“…This result was similar to a previous study in Arabidopsis where more than 90% suppression of the reporter gene was achieved (Hiratsu et al 2004). Recently, CRES-T was successfully applied to several horticultural plants including torenia (Narumi et al 2008; Sasaki et al in this issue), morning glory (Ono et al in this issue), and cyclamen (Tanaka et al in this issue). The EAR motif is conserved among a wide range of higher plant species, including Arabidopsis, rice, tobacco, petunia, and wheat (Ohta et al 2001).…”
Section: Repression Activity Of Srdx Domain In Transientexpression Assupporting
confidence: 78%
See 2 more Smart Citations
“…This result was similar to a previous study in Arabidopsis where more than 90% suppression of the reporter gene was achieved (Hiratsu et al 2004). Recently, CRES-T was successfully applied to several horticultural plants including torenia (Narumi et al 2008; Sasaki et al in this issue), morning glory (Ono et al in this issue), and cyclamen (Tanaka et al in this issue). The EAR motif is conserved among a wide range of higher plant species, including Arabidopsis, rice, tobacco, petunia, and wheat (Ohta et al 2001).…”
Section: Repression Activity Of Srdx Domain In Transientexpression Assupporting
confidence: 78%
“…In this system, a transcription factor is converted from activator into a repressor by fusion to the EAR motif (SRDX), and this repressor dominantly suppresses the expression of the target genes of the transcription factor (Hiratsu et al 2003). Suppression by CRES-T has been successful in a wide variety of monocots and dicots including Arabidopsis, torenia, morning glory, cyclamen, and rice (Mitsuda et al 2006;Narumi et al 2008; some articles in this special issue). Chimeric repressors have been applied to various transcription factors, including those that regulate morphological development: CUP SHAPED COTYLEDON1 (Hiratsu et al 2003), TCPs (Koyama et al 2007), AGAMOUS (Mitsuda et al 2006;Narumi et al 2008;Xu et al 2006) (Hiratsu et al 2003); and secondary wall formation: NSTs (Mitsuda et al 2007(Mitsuda et al , 2008.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Narumi et al (2008) showed that a gene silencing technology targeting transcription factor, Chimeric REpressor gene-Silencing Technology (CRES-T; Hiratsu et al 2003), functioned in torenia. The CRES-T system could become a powerful tool for suppressing transcription factor genes in torenia.…”
Section: Future Prospectsmentioning
confidence: 99%
“…Several of the transgenic plants created using the CRES-T system exhibited recognizable phenotypes and among these, the alteration of flower shape is particularly well-suited to experimental purposes Narumi et al 2008;Ohtsubo 2011). We used A. thaliana TFs for the CRES-T system because A. thaliana TFs are well studied compared with those of I. nil.…”
mentioning
confidence: 99%